(untitled) (American Journal of Applied Statistics and Economics, 2025)
This study examines how key macroeconomic variables such as GDP growth, inflation, interest rates, government debt and unemployment influence government spending in Ghana. While many studies rely on traditional econometric models, this research applies a Bayesian regression framework, which allows for the incorporation of prior information and a clearer assessment of uncertainty in the estimates. The results show that GDP growth, public debt and unemployment are positively associated with government spending, while higher interest rates constrain fiscal expenditure. The effect of inflation remains uncertain. These findings provide new evidence on the dynamics of fiscal behavior in Ghana and highlight the need for policymakers to balance growth and debt considerations while managing the risks of rising interest rates. The study contributes to the broader debate on how macroeconomic conditions shape fiscal policy in emerging economies.